Higgs candidates in e+e- interactions at √s = 206.6 GeV - Dova, María Teresa (2000)
In a search for the Standard Model Higgs boson, carried out on 212.5 pb−1 of data collected by the L3 detector at the highest LEP centre-of-mass energies, including 116.5 pb−1 above GeV, an excess of candidates for the process is found for Higgs masses near 114.5 GeV. We present an analysis of our data and the characteristics of our strongest candidates.